An analysis of the steam curing and autoclaving process parameters for reactive powder concretes. (30th January 2017) - Zdeb, Tomasz
Graphical abstract: Highlights: The optimum RPC steaming and autoclaving parameters were determined. The efficiency of steel fibres depending on RPC curing conditions was investigated. The changes in microstructure of RPC cured at elevated temperature were described. Abstract: The two different methods of thermal treatment were used when curing reactive powder concretes (RPC), namely low-pressure steam curing and autoclaving. The properties of obtained material were referred to those of materials cured in water at a temperature of 20 °C. The main aim of this study is to verify mechanical properties of RPC without fibres, at variable steaming and autoclaving parameters. The following factors were taken into account: preset time, target temperature and holding time. At the same time by using the techniques of SEM and MIP, changes in microstructure of composites cured at an increasing temperature and different time were observed. After establishing the most favourable heat treatment parameters, their effect on the efficiency of steel fibres of 6 mm long added at amount of 2% by volume was analysed. Compressive strength and three-point flexural strength were tested along with deformability evaluation. The factor having the strongest effect on mechanical properties of RPC under examination was the target temperature of steaming and autoclaving. RPC curing conditions had also a significant impact on post-critical strains in composites containing dispersed reinforcement.